Predicting sulphur dioxide dispersion from multiple sources in major cities in Klang Valley, Malaysia using integrated MM5-SMOKE-CMAQ model system - Ching, Loi Kok (2011)
The emission of sulphur dioxide has increased along with the industrialization and urbanization which become the public’s major concern. It is well known as the precursor of acid precipitation, which could bring negative impacts on the environment and human health. It is important to have a reliable estimation of sulphur dioxide emissions in order to formulate effective strategies for mitigation purposes. Hence, emission source estimation and air quality assessment using air quality modeling system becomes essential in the process of developing an appropriate air quality plans. The goal of the study will be focused on the relationship between pollution emission changes and the meteorological condition thus affecting the air quality in the study area. The primary objectives of the study is to establish an emission inventory from different types of sources in Klang Valley, to simulate meteorological and dispersion of sulphur dioxide in Klang Valley region using integrated model MM5-SMOKE-CMAQ, and evaluate the performance of the model. Simulation on the meteorology condition using Fifth Generation Mesoscale Model (MM5) was carried out and emission inventory was simulated using Sparse Matrix Operational Kernel Emission (SMOKE) model. The meteorological profiles from MM5 and emission data from SMOKE model were used to simulate the dispersion of sulphur dioxide using Community Multiscale Air Quality (CMAQ). The evaluation of CMAQ model revealed that the model performed better in 12-hour averaged sulphur dioxide concentration with high correlation value of 0.87 and low RMSE of 1.87E-03 ppmv. These results justify the use of integrated model MM5- SMOKE-CMAQ modeling system in the Klang Valley region which has complex terrain and land use. The model showed maximum SO2 concentration (0.041ppmv) was located at Shah Alam industrial zone, followed by Klang industrial zone and other cities such as Kajang, Petaling, Gombak and Cheras showed relative low SO2 concentration. The model also showed that the highest level of sulfur dioxide was well below the guideline recommended by DOE (0.14ppmv).